Educating the Rabbani Generation: A Diffusion of Islamic Scholars Through Participatory Action Research - Syahri Ramadona; Amida zahirah; Izzatil Qur’ani; Lusi Yana Dewi; Nadia Rofian Dini; Sakinah Mawaddah (ASSUNNAH PRESS, 2022)
This research focuses on three discussion objectives: First, how to create a rabbani environment in a still strong society with local culture and customs. Second, activities that can help parents educate their children according to Islamic law. Third, how to instill a love for the Al-Qur’an and religion in children. Community service aims to create human resources that benefit the nation and religion. The community service in the village of Alam Panjang uses an alternative participatory action research (PAR) approach. Data is obtained by making observations in cycles where it is hoped there will be changes at each stage. The expected changes are supported by providing programs such as tahfiz and tahsin guidance, learning Arabic, spiritual cleansing, and constructive motivations. From the implementation of actions in the form of activity programs, satisfactory results were obtained. These results are an increase in willingness and achievements in tahfiz, tahsin, learning Arabic, and spiritual cleansing. Community service positively impacts people's mindset, which is no longer limited to things that naturally exist but makes them open to advancing human resources. This study clearly shows that the research conducted through this community service activity has improved the quality and human resources in the village of Alam Panjang.